2021
DOI: 10.3390/ani11041063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cornus and Its Mixture with Oregano and Thyme Essential Oils on Dairy Sheep Performance and Milk, Yoghurt and Cheese Quality under Heat Stress

Abstract: The effect of a diet supplemented with a novel cornus extract, enriched with essential oils of oregano and thyme, on the performance of Chios cross-bred dairy sheep was investigated during the summer period. The plant extracts were prepared using a “green” method based on aqueous extraction. A total of 45 lactating ewes were allocated into three equal groups in a randomized block design. The three groups were fed the same feed allowance, roughage based on Lucerne hay and wheat straw and a concentrate based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Particularly in small ruminants, some studies have evaluated the effect of dietary inclusion of EOs on animal performance [15,16], nutrient digestibility, ruminal fermentation [17,18], blood biochemistry [19,20], and meat quality [21,22], as well as milk production and composition [23,24]. However, no conclusive results have been obtained until now, perhaps due to the variability that exists among these studies regarding the experimental periods, primary bioactive compounds, and the doses of EOs used [25].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in small ruminants, some studies have evaluated the effect of dietary inclusion of EOs on animal performance [15,16], nutrient digestibility, ruminal fermentation [17,18], blood biochemistry [19,20], and meat quality [21,22], as well as milk production and composition [23,24]. However, no conclusive results have been obtained until now, perhaps due to the variability that exists among these studies regarding the experimental periods, primary bioactive compounds, and the doses of EOs used [25].…”
Section: Introductionmentioning
confidence: 99%
“…Using extruded feed additives in the diet had a positive effect on the health condition of the goats and their external characteristics, so that the goats of the experimental groups had a visually different coat. With poor feeding, improper maintenance and diseases of animals, wool easily loses its natural shine (Kalaitsidis et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…But increasing mixture of additives to 6g/cow per day leads to negative effects. Kalaitsidis et al (2021) studied the effect of Cornus essential oils and its mixture with oregano and thyme essential oils on the productivity of dairy sheep and the quality of milk, yogurt and cheese under heat stress. The results showed that including the plant extracts and essential oils increased milk production.…”
Section: Resultsmentioning
confidence: 99%
“…However, the dietary administration of 1200 mg of rosemary extract increased milk performance, considering the high productivity of Valle del Belice ewes, and also sustained body condition score [78]. Moreover, dairy ewes of the Chios cross-breed treated during summer by adding a specific cornus, a Mediterranean plant rich in anthocyanins, gallic acid, and ellagic acid with a high antioxidant activity, into the EO compounds of oregano and thyme, displayed higher milk production, lower milk urea concentration, and SCC [79]. In addition, the supplementation of cornus hydrodistillation extract, as well as oregano and thyme essential oils, improved the oxidative stability of milk, even though it did not affect the milk fatty acid profile.…”
Section: Effects Of Essential Oils On Small Ruminant Productsmentioning
confidence: 97%
“…Murcia al Vino cheese, without affecting cheese yield, microbiological count, and sensory parameters [83]. The addition of cornus hydrodistillation extract, as well as oregano and thyme essential oils, improved the oxidative stability of Feta cheese and yoghurt, with no effects on their fatty acid profile [79].…”
Section: Effects Of Essential Oils On Small Ruminant Productsmentioning
confidence: 99%